1994
DOI: 10.1017/s0022143000012417
|View full text |Cite
|
Sign up to set email alerts
|

The role of the margins in the dynamics of an active ice stream

Abstract: ABSTRACT. A transverse profile of velocity was measured across Ice Stream B, West Antarctica, in order to determine the role of the margins in the force balance of an active ice stream. The profile extended from near the ice-stream center line, through a marginal shear zone and on to the slow-moving ice sheet. The velocity profile exhibits a high degree of shear d eformation within a marginal zone, where intense, chaotic crevassing occurs. Detailed analysis of the profile, using analytical and numerical models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
159
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 25 publications
17
159
1
1
Order By: Relevance
“…The steep, up-ice surface gradient of the Isbrae drives large shear stresses within it. As there is no deformable bed, initial research suggested that internal ice deformation was the main mechanism of ice motion (Echelmeyer & Harrison 1990;Iken et al 1993;Echelmeyer et al 1994). More recent work, however, suggests that large driving stresses (c. 200-300 kPa) cause basal melt rates that account for up to 60% of surface movement through basal motion (Truffer & Echelmeyer 2003), while deformation of the lowest 1700 m of 'softer' Wisconsin-age ice is thought to account for the rest of the Isbrae's high surface velocity (Luthi et al 2002).…”
Section: Jakobshavns Isbraementioning
confidence: 99%
“…The steep, up-ice surface gradient of the Isbrae drives large shear stresses within it. As there is no deformable bed, initial research suggested that internal ice deformation was the main mechanism of ice motion (Echelmeyer & Harrison 1990;Iken et al 1993;Echelmeyer et al 1994). More recent work, however, suggests that large driving stresses (c. 200-300 kPa) cause basal melt rates that account for up to 60% of surface movement through basal motion (Truffer & Echelmeyer 2003), while deformation of the lowest 1700 m of 'softer' Wisconsin-age ice is thought to account for the rest of the Isbrae's high surface velocity (Luthi et al 2002).…”
Section: Jakobshavns Isbraementioning
confidence: 99%
“…Calculations of ice velocity can be easily extended in the transverse direction, yielding distribution of ice velocity along a transverse crosssection (Raymond 1996, equation 38). This approach is appropriate for firstorder modeling of an ice-stream flow, whenever longitudinal stresses can be ignored (Echelmeyer et al 1994;Harrison et al 1998;Jackson & Kamb 1997;Van der Veen & Whillans 1989b;Whillans et al 1989). This approach is appropriate for firstorder modeling of an ice-stream flow, whenever longitudinal stresses can be ignored (Echelmeyer et al 1994;Harrison et al 1998;Jackson & Kamb 1997;Van der Veen & Whillans 1989b;Whillans et al 1989).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Equation (1) assumes that the driving stress is balanced by a combination of spatially uniform basal resistance and marginal stress. This approach is appropriate for firstorder modeling of an ice-stream flow, whenever longitudinal stresses can be ignored (Echelmeyer et al 1994;Harrison et al 1998;Jackson & Kamb 1997;Van der Veen & Whillans 1989b;Whillans et al 1989).…”
Section: Model Descriptionmentioning
confidence: 99%